Die Reihe Merz 1923-1932 - Schwitters, Kurt (Kurt Schwitters. Alle Texte, 2019)
This volume, the fourth in the complete works of Kurt Schwitters, offers the first complete and annotated edition of Merz, the avant-garde journal for multimedia that appeared between 1923 and 1932 under Schwitters' editorial direction. The volume also includes scholarly contributions that extensively examine the journal's contents, structure and design from an interdisciplinary perspective.